(untitled) (Amsterdam, 2016)
Advances in Structure and Activity Relationship of Coumarin Derivatives covers the structural behavior of various coumarin derivatives for various potential pharmaceutical applications. Based on substitution targeted for active sites, the book takes a rational approach for designing new and specific potent drugs, optimizing existing ones, and developing novel reactions. This focused primer describes the chemical structure and activity of coumarin derivatives to explore the effects of different substituents at specific positions, and their properties for effective bioactivity.
Quan hệ cấu trúc và hoạt tính sinh học
Keywords: Structure-Activity Relationship,Mối quan hệ cấu trúc-hoạt động